Trends in digitalization of financial and economic activities of companies in Ukraine - A.Yu.; M.Р.; S.М.; I.V.; O.А. (Економіка, управління та адміністрування)
Introduction. The article examines the issue of the digital transformation of Ukrainian businesses. Despite the existing developed sector of information technology, domestic companies have a low level of digitalization of their activity. The methodological basis of the study were general and special research methods, including methods of theoretical generalization, analysis, synthesis, comparison and others. The information base of the study was the data of the State Statistics Service of Ukraine, National Bank of Ukraine, research of international organizations, scientific papers and other open sources.